Unlikely Partners: Salvo d'Angelo, David O. Selznick, and Zavattini's 'Stazione Termini'. (4th May 2019) - Bonifazio, Paola
ABSTRACT: This essay analyses documents collected at the Harry Ransom Center that pertain to Italian producer Salvo d'Angelo, in particular his correspondence with David O. Selznick in 1950–51 regarding a proposed French–Italian–American co-production of Stazione Termini. The goal of this essay is to contribute, on one hand, to current scholarship on the history of the Italian film industry. At the same time, the case of Salvo d'Angelo's failed agreement with Selznick constitutes a lens through which to examine the issue of film 'authorship' at a crucial juncture in the history of Italian cinema, in the context of growing entrepreneurship in the industry and the rise of Italian (male) directors on the international scene.